ANALISIS PERBANDINGAN SIMPANGAN STRUKTUR BAJA PASAR RAKYAT BANYUASRI DI BULELENG PADA MODEL DENGAN DAN TANPA BASEMENT - I Made Griadi Dharma Putra; I Putu Ellsa Sarassantika; Kadek Windy Candrayana (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2025)
Development in Indonesia is currently experiencing very rapid development, with the development of technology in the construction sector, to meet the aesthetic aspects of buildings and due to limited land, it is planned that building construction will be multi-storey. In the planning and design of multi-storey buildings, the decision to include or not include a basement has significant implications for the structural behavior of the building, particularly in relation to lateral drift and overall stability. Lateral drift, or horizontal shift between levels, is a crucial parameter in ensuring the comfort and structural integrity of buildings when facing lateral loads such as earthquakes. Comparative analysis between these two models is important to understand the influence of the presence of a basement on the dynamic response of a building. The main focus is to evaluate the extent to which the presence of a basement influences the lateral stiffness and dynamic response of the building. Analysis shows that the drift value produced by the model without basement is smaller than the model with basement. Namely, the maximum value for the model without a basement is 17.3 mm and the model with a basement has a maximum value of 29.1 mm with a clearance of 54.6 mm on the 3rd floor in the x direction and in the Y direction. The maximum value for the model without a basement is 25.4 mm and the model with a basement has a maximum value of 43.6 mm with a clearance of 54.6 on the 3rd floor. Based on the results of the analysis that has been carried out, it shows that both models have met the earthquake resistance requirements such as base force. seismic, permissible deviations between floors, capital, and mass inclusions. Keywords: Steel structure; drift; etabs; models without basement; models with basement